"Hello, can you hear me?": Narratives of online mental health counselling among Filipino adults during the pandemic. Issue 1 (5th November 2022) - Dela Cruz, Edlene Nicole M.; Marcelo, Rohann Cris A.; Naling, Bea Ysabelle M.; Ty, Welison Evenston G.
Abstract: Filipinos are often reluctant to seek professional mental health (MH) help. However, literature reveals that online counselling is preferable to face‐to‐face (F2F) MH services, with the pandemic possibly magnifying technology's anonymity and disinhibiting benefits. To further explore facilitators of online MH help‐seeking, this study tapped into the lived stories of Filipino adults who experienced at least one counselling session from March 2020 to March 2022. Among 83 screened respondents, 11 semistructured interviews were transcribed and analysed following Crossley's (2000) method. Findings reveal an overarching online MH counselling narrative composed of three phases and their respective events: (a) Precounselling ( Resiliency Narrative versus MH Awareness, Turning Point, and Linking versus Searching ); (b) Counselling ( Two‐way Introduction, Unloading and Untangling, and Decision to Maintain or Terminate ); and (c) Postcounselling ( Relapse and Journey towards Growth and Advocacy ). Three all‐encompassing facilitators were embedded throughout the process: Autonomy, Financial Capability, and MH Institutions . Notably, participants attributed their MH help‐seeking to autonomy, despite culture and stigma, because of enabling environments that entail heightened MH literacy, positive past experiences with professional MH help, social support and encouragement, and a sense of shared reality. Benefits unique to online counselling were also apparent among participants' narratives, including alleviating geographical boundaries and added financial and personal pressures. Overall, findings posit that Filipino adults consider online counselling as a preferable alternative to F2F counselling, thus necessitating further development and institutional support.